Opting out: confidentiality and availability of an 'alibi' for potential living kidney donors in the USA. Issue 7 (3rd November 2014) - Thiessen, Carrie; Kim, Yunsoo A; Formica, Richard; Bia, Margaret; Kulkarni, Sanjay
Abstract : Ethicists and guidelines have suggested that potential living kidney donors who withdraw from evaluation be offered an 'alibi.' We sought to determine what potential living kidney donors are told about their ability to opt out, alibi availability and postwithdrawal confidentiality. We reviewed 148 consent forms for living kidney donor evaluation from US transplant centres that performed >5 living kidney transplants in 2010–2011 (response rate 87%). We found that while 98% of centres used evaluation consent forms that indicated that the donor could withdraw, only 21% of these documents offered an alibi. Another 23% of centres' consent forms indicated that the transplant team would be willing to inform the intended recipient that an individual was not a potential donor. Relatively few consent documents explicitly addressed the confidentiality of the donor's health information (31%), candidacy status (18%), decision (24%) or reasons (23%) following withdrawal. To preserve potential donors' autonomy and relationships, we advocate that all transplant centres offer general alibis in their evaluation consent forms. We conclude by offering recommendations for evaluation consent discussions of opting out, alibis and postwithdrawal confidentiality.